ENGLISH AS A BRIDGE TO GLOBAL CITIZENSHIP: A CIVIC EDUCATION PERSPECTIVE IN SEKOLAH KARAKTER - Ajisoko, Pangkuh; Misbahudin (Esteem Journal of English Education Study Programme, 2025)
This research investigates the synergy between English language learning and civic education, emphasizing the cultivation of global citizenship through the Pancasila Student Profile within Indonesia’s Merdeka Curriculum. In the era of accelerating globalization, mastery of English emerges as an essential competency, enabling students to participate meaningfully in international discourse while safeguarding their national identity. The study explores how English instruction can function as a conduit for embedding values of cultural pluralism, tolerance, and cross-border collaboration. Using a case study at Sekolah Karakter, it examines the feasibility and impact of integrating English language pedagogy with Citizenship Education (PPKn) to strengthen students’ comprehension of global citizenship while preserving indigenous wisdom. Findings reveal that the fusion of thematic and project-based learning in both English and PPKn settings deepens students’ engagement with global challenges, nurtures empathy, and fortifies their patriotic consciousness. The research concludes that a well-orchestrated integration of English and civic education holds significant potential in shaping learners who are both globally attuned and firmly anchored in their cultural heritage.